2009
DOI: 10.1002/macp.200800543
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Development of Polymer Blends in Extruder: The Effects of Compatibilization and Rotation Rate

Abstract: The effects of reactive compatibilization and extruder rotation rate on morphology development of polymer blends are studied. Morphology develops faster in compatibilized blends than that in their uncompatibilized counterparts. Based on force analysis, it has been proved that compatibilization facilitates dispersion by reducing slip at the interface of polymer phases. Rotation rate influences the morphology development of polymer blends by changing the residence time of polymers in the extruder. For uncompatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…The final shape and size of the dispersed phase not only depend on the processing parameters but also on the properties of the polymer. Earlier studies concerning the effects of polymer compositions, viscosity/elasticity ratio, shear rate, processing time and temperature on the morphology development of polymer blends mainly focused on the drop deformation, break up, and coalescence [26–28]. It has been proved that an elongational flow was more effective in deforming particles than shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…The final shape and size of the dispersed phase not only depend on the processing parameters but also on the properties of the polymer. Earlier studies concerning the effects of polymer compositions, viscosity/elasticity ratio, shear rate, processing time and temperature on the morphology development of polymer blends mainly focused on the drop deformation, break up, and coalescence [26–28]. It has been proved that an elongational flow was more effective in deforming particles than shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the interfacial tension between molten metals and thermoplastics is expected to be much higher than between immiscible homopolymers although we are unaware of experimental measurements of the same. Third, compatibilizers are very commonly used when blending immiscible homopolymers , whereas to our knowledge, compatibilizers have not been developed for blending LMPA with thermoplastics. For both the preceding reasons, it may be more difficult to achieve an intimate dispersion of the LMPA and the polymer.…”
Section: Preparation and Morphology Of Lmpa‐filled Polymer Compositesmentioning
confidence: 99%
“…86 In the literature on the neat polymer blends, it has been shown that most of the signicant morphology development happens at the very early stages of mixing. [67][68][69][70]73,[87][88][89][90][91] Favis 88 showed that extending the mixing time to 20 min for polypropylene:polycarbonate (PP:PC) inside a batch mixer did not generate further droplet size reduction. The results were the same in a wide range of torque/viscosity ratios of the polymer blend constituents.…”
Section: Morphology Development During Mixing In Internal Batch Mixermentioning
confidence: 99%